Development of a hybrid simulation and emulation testbed for VANETs - Costa, R. (2009)
In the area of Intelligent Transportation System traffic efficiency and safety for users have become very popular topics and have triggered extensive research in Vehicular Ad-Hoc Networks (VANETs). Traditional methods for research and development like field testing and simulation have been used. But field testing is usually very expensive and simulation lacks accuracy in wireless environments. This article aims to introduce a hybrid solution that combines the simulation and emulation methods. The proposed solution is implemented in a testbed for VANETs. The resulting testbed would allow multiple real routing instances to run simultaneously on a simulated environment. And to provide performance measures such as resource consumption and scalability.